A method for characterizing stapes prostheses by their mechanical transfer function - Sutor, Alexander; Hornung, Joachim; Goßler, Julian; Döllinger, Michael; Lerch, Reinhard (Medical Engineering & Physics, 2012)
In this contribution, we present and evaluate a method for characterizing stapes prostheses by their mechanical transfer function. The measurements were carried out after a stapedotomy surgery was performed in three human temporal bones conserved in 4% formaldehyde. The inner ear was drained of fluid. Successively, one of three different stapes prostheses was inserted. After such preparation, the prosthesis piston movement compared to the incus movement is measured with laser vibrometry. The magnitude transfer function considered is defined as the amplitude of the prosthesis piston movement compared to the amplitude of the incus movement. Measurements were made in a frequency range from 500 Hz to 4 kHz. The measured amplitudes roughly ranged between 10 nm and 100 nm. A great advantage of the presented method is the fact that only a small portion of the ossicular chain influences the measurement, mainly the joint between the prosthesis and the incus. Furthermore, the usage of cadaver temporal bones allows for an automated measurement setup, long term experiments and the access of measurement positions inapproachable during in vivo measurements. With this method, the different kinds of prostheses could be evaluated on incuses of different diameters. (C) 2012 IPEM. Published by Elsevier Ltd. All rights reserved.
Keywords: Otosclerosis; Stapes prosthesis; Crimping; Mechanical transfer function; Laser vibrometer